Conglomerate Mergers and Concentration Ratios - Goldberg, Lawrence G. (The Review of Economics and Statistics, 1974)
Lean management and transaction management offer complementary perspectives on cost reduction to the business organization.Lean management focuses on preventing waste in production and is drawn from the business practice.The focus of transaction management is a reduction of transaction costs in the internal and external organization of the firm.The emphasis is on value creation on the long run.Transaction management is based on the theories of transaction cost economics and the new institutional economics.From these theoretical perspectives, with tree Nobel prize winners as originators (Coase, North and Williamson), it may contribute to the strategic management of the firm.